Equal Rules, Unequal Effects: Challenging Member State Equality Through One-Size-Fits-All Regulations - Savčić, Sanja (Unequal Equals? The Status of Member States in an Integrating European Union, 2026)
The EU aims to improve the living and working conditions of its citizens while fostering economic unity, with a particular focus on reducing regional disparities. The EU holds exclusive competence in certain areas, with Member States only able to legislate when authorised or required by EU law. In areas of shared competence, both the EU and Member States can legislate, but Member States must act only when the EU has not already exercised its authority. Although the EU does not have general competence over private law, it harmonises certain aspects of private law to support its broader objectives. The EU primarily uses directives to regulate general private law, allowing flexibility for Member States to adapt laws to their legal systems. However, the shift towards regulations is seen as a response to the interconnectedness between trade and private law, promoting uniformity across Member States. This approach enhances the single market but raises questions about its compatibility with diverse national legal traditions. The effectiveness of this regulatory shift in promoting equality will depend on the EU’s ability to balance uniformity with respect for national legal practices. This chapter also aims to evaluate the development trends in the unification of law and their outcomes, presented through an explanatory study of the General Data Protection Regulation, an act that has changed not only the legal framework for the protection and processing of personal data but also the business environment. Given that Member States do not have the economic strength as the EU, a question has arisen as to whether the regulation has limited the ability of some states to shape an appropriate but protective framework for their own economic interests.